PERANCANGAN BUSANA CONVERTIBLE UNTUK BRAND VOLATILE - Felicia Setiawan; Paulina Tjandrawibawa (Jurnal Vicidi, 2016)
The collection is created to introduce convertible clothing owned by Volatile brand. Young people are physically active and visit several places in one day due to their activity. Therefore, Volatile brand provides a solution to above type of consumers who need practical clothing by creating multifunction convertible clothing. Volatile clothes can give more than one look in which consumers can change their look in short time.